Yahoo Web Search

  1. Sort by

  1. k^2 - 3k = 28 k^2 - 3k - 28 = 0 (k - 7)(k + 4) = 0 k = -4, 7 and if you're asked to find x: k = -4: -4 = (x + 3)/(x - 4) -4(x - 4) = x + 3 -4x + 16 = x + 3 16 - 3 = x...

    2 Answers · Science & Mathematics · 18/08/2019

  2. ... SOLUTION: I like to use this notation: C(n, k) = n! / [(n - k)! k!] That would mean: C(n, n - k) = n! / [(n...;--> {A, B, C} So C(n,k) = C(n, n-k)

    6 Answers · Science & Mathematics · 12/09/2019

  3. ... tangent lines of form y = 6x + k have slope 6  Set slope dy/dx = 7/[2√(x)] = 6  x = 49... how that applies here  (y/7)^2 = x = (y – k)/6  6y^2 = 49y – 49k  6y^2 - 49y + 49k = 0  49*49 = 4*6*49k...

    3 Answers · Science & Mathematics · 29/01/2020

  4. -365.05 F is 52.57 K -365.10 F is 52.54 K <== this is ...

    2 Answers · Science & Mathematics · 11/07/2019

  5. ...question. Notice that the question says, "for what *values* of k..." You did what most people know to do which is to use the...

    3 Answers · Science & Mathematics · 01/11/2019

  6. K-pop has nothing to do with music. I'm not sure what the attraction is but it isn't the music.

    2 Answers · Entertainment & Music · 06/09/2019

  7. Hint: Let u = k-9. Then write all as an expression as u. Then let u=k. Show ur steps if need be and we can take it from there. 

    3 Answers · Science & Mathematics · 13/11/2019

  8. then f(-2) = 0 or (-2)^4 - k*(-2)^3 + 1 = 0 16 - 8k + 1 = 0 k = -17/8

    2 Answers · Science & Mathematics · 07/06/2019

  9. f = 1/(2 * π) * √(k/m) The first step is solve problem 20 to determine the spring constant... to determine the increase of the length. ∆ L = 0.15 – 0.10 = 0.05 meter k = 4 ÷ 0.05 = 80 N/m Now we can use the spring constant to calculate the...

    2 Answers · Science & Mathematics · 16/08/2019

  10. from the arrhenius equation .. k = Ao exp(-Ea / RT) for 2 conditions of different ...

    1 Answers · Science & Mathematics · 09/02/2020

  1. Ad
    related to K
  1. Try asking your question on Yahoo Answers